Data for: Lava crickets (Caconemobius spp.) on Hawai´i Island: first colonizers or persisters in extreme habitats? - Heinen-Kay, Justa; Rotenberry, John; Kay, Adam; Zuk, Marlene (Dryad, 2020)
1. Primary succession after a volcanic eruption is a major ecological
process, but relatively little is known about insects that colonize barren
lava before plants become established. 2. On Hawai´i Island, the endemic
cricket, Caconemobius fori Gurney & Rentz, 1978, is known as the
first multicellular life form to colonize lava after an eruption from
Kīlauea Volcano. In the Kona region, a congener, Caconemobius anahulu
Otte,1994 inhabits unvegetated lava flows from Hualālai Volcano, but
little has been documented about its distribution. 3. Our aim was to
characterize the presence/absence of Caconemobius spp. across lava flows
that are largely unvegetated, but differ in age since eruption and
connectivity to older flows. We used baited live traps to survey 9
month–50 year-old Kīlauea lava flows for C. fori, and ~220 year-old
Hualālai lava flows for C. anahulu. 4. We found no evidence that C. fori
has colonized the Kīlauea flows from the 2018 eruption. However, we did
discover that C. fori was persistent and widespread on Kīlauea lava up to
50 years old within Hawai´i Volcanos National Park. We also captured C.
anahulu across much of the Hualālai lava flows we surveyed in Kona. 5. We
demonstrated that C. fori do not always arrive on new lava within months
after an eruption, in contrast to previous reports, and that both C. fori
and C. anahulu can remain on lava longer than previously appreciated.
Vegetation successional state may be more important than true age for the
persistence of these endemic crickets.
Detailed methods can be found in Heinen-Kay et al. (2021) Ecological
Entomology. In short, we sampled for two species of endemic Caconemobius
crickets on mostly barren lava on Hawaii Island. We used live traps baited
with shrimp paste. Sampling sites were distributed among three
regions:  C. anahulu was present in Kona, C. fori was present in
HVNP, and C. fori was expected to be present in Puna.
Trap histories for Caconemobius on the Big Island of Hawai’i,
2019.  Data accompanies Heinen-Kay et al. (2021) Ecological
Entomology, which details the sampling design.  Each line
represents a single trap that was open for 1 to 5 nights, beginning on the
date given.  “1” represents a trap-night on which a Caconemobius
was captured, “0” a trap-night on which one was not.  Sampling
sites were distributed among three regions:  C. anahulu was
present in Kona, C. fori was present in HVNP, and C. fori was expected to
be present in Puna.